(untitled) (Nordic Journal of African Studies, 2008)
Language assessment serves many purposes in society, such as a means for achieving national language policy goals. It is a tool in language teaching; can motivate learning; and supports the connections between language learning, literacy development and cognitive development. In Nigeria, poor exam performance and low level English proficiency indicate that language teaching and assessment have not sufficiently engendered effective language use. Summative language assessment is practised in ways that hold learners responsible for not learning what is not taught or is improperly taught. Thus, since local languages play little or no role in personal advancement, the society is unable to utilize potential manpower sidelined by poor achievement in English language tests. It is therefore now imperative that the examining bodies and curricula designers appraise their philosophies and practice with a view to aligning language teaching and assessment with national development goals and international best practice.